Strategi Penyelesaian Non Performing Financing Pada KSPPS BMT di Kabupaten Jepara - Hazmi, Faiqul; Sofwan, Ali; Hidayat, Solikhul (Al-Intaj : Jurnal Ekonomi dan Perbankan Syariah, 2023)
High number of non performing financing (NPF) has a negative impact on Islamic Microfinance (BMT), that problems affect to financial performance in low condition, liquidity problems, as well as difficulties in covering operational costs, difficulties to payback financial obligations, and BMT will eventually losses then will be converted by reducing the amount of capital. That things will be resulting in the threat of sustainability. The aims of this study, are explain the strategies used by BMT`s in Jepara to solve their NPF. The research method used a descriptive qualitative approach, this research used purposive sampling, the criteria is the key person in carrying out steps to resolve NPF in their institutions. The research finding is, there are strategies to overcome the problems of high NPF. The strategy used by 2 models, first preventive action in the form of forming strong financing organs and carrying out effective financing analysis second curative action after the financing is disbursed (1) Customer Nurturing (2) Rescheduling, (3) Reconditioning, (4) Restructuring, (5) Collateral Confiscation through litigation and non-litigation. Other findings is (6) The strategy as solution through the organizational path that became afiliation of the KSPPS BMT.